THE EFFECTIVENESS OF USING STUDENT TEAM ACHIEVEMENNT DIVISION (STAD) AS STRATEGY TO INCREASE STUDENTS COMPETENCE TO READING COMPREHENSION TO THE THIRD GRADE AT SMP SWASTA HANGTUAH STABAT IN ACADEMIC YEAR 2021/2022 - Febby Aryanti Pratiwi; Eka Rahmadanta Sitepu; M Dian Wahyudi (Jurnal Serunai Bahasa Inggris, 2022)
This research deals with the effect of Student Team Achievement Division (STAD) as strategy to increase student competence in students’ reading comprehension. The objectives of this research was to find out if there was a significant effect of Student Team Achievement Division (STAD) strategy to increase students competence in students’ reading comprehension. It was conducted by using experimental research. The population of this research was the third year students of SMP Swasta Hangtuah Stabat consists of two classes. Two classes were taken as the sample of this research, IX-1 and IX-2. The class of IX-1 was an experimental class and IX-2 was a control class. The number of sample was 62 students. The experimental class was taught by Student Team Achievement Division (STAD) as strategy, otherwise the control class was did not got treatment. The instrument for collecting the data was reading comprehension test. The calculation revealed that the hypothesis about significant difference on reading comprehension between students classes who were taught Student Team Achievement Division (STAD) and those who are did not got treatment. It means that there was a significant effect of Student Team Achievement Division (STAD) strategy to increase students competence in students’ reading comprehension of the third grade students of SMP Swasta Hangtuah Stabat in academic year 2021-2022.